Barack Obama - Krensky, Stephen (New York DK Pub, 2010)
Presents the life of Barack Obama, including his childhood in the United States and abroad, careers as a community organizer and lawyer, and his election as the forty-four president in 2009
Includes bibliographical references (p. 124) and index
1 2 13
Keywords: Obama, Barack -- Juvenile literature; Presidents -- United States -- Biography -- Juvenile literature; Obama, Barack; Presidents